Special Economic Zones and China's Development Path - Tao, Yitao (Research Series on the Chinese Dream and China's Development Path,, 2018)
The book provides insights into the development of special economic zones, which are an important factor in the political and economic reforms in China. It discusses a number of topics, including the history and the modernization of special economic zones in China, the contributions of special economic zones to China's economic success and cultural change, as well as the new mission of special economic zones in the current economic-social context. Applying institutional economics and growth poles theory, it discusses the mechanism of China's path driven by special economic zone practices. The book is a valuable resource for researchers interested in special economic zones, political and institutional reforms and economic transformation during China's modernization.